BACKGROUND CYCLICAL TECHNICAL MAINTENANCE ELECTRIC VEHICLE TRANSPORT - , М. В., С. О. (Municipal economy of cities. Series: «Economy science», 2013)
We consider the recurrence of vehicle maintenance and repair effects and preventive interventions for them in the current state enterprises electric Ukraine.